MULTIPLE INTELLIGENCE AND MATHEMATICAL CREATIVE THINKING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Mimin Ninawati; Didi Suryadi; Tatang Herman; Ari Metalin Ika Puspita (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
One of the uniqueness of students is their intelligence. Intelligence affects students' thinking abilities in following the learning process. This study aimed to analyze the relationship between multiple intelligence and mathematical creative thinking abilities of elementary school students. The population in this study were fourth grade students at SDN Lenteng Agung 01 Pagi, South Jakarta, Indonesia. Based on the simple random sampling technique used, it was obtained 50 students as research samples. Mathematical creative thinking ability was measured using tests while multiple intelligence was measured using questionnaire. The collected data was then tested for correlation using the Pearson product moment correlation test and the simple correlation coefficient significance test (t test). From the results of the analysis using Pearson correlation, it was obtained a correlation coefficient of 0.546. The correlation coefficient obtained was then tested for significance and the value of t count obtained was 4.518 (t count 4.518> t table 0.346). These results indicated that there was a significant relationship between multiple intelligence and mathematical creative thinking abilities of elementary school students.